(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
In the article, the use of lexical units of the mastery layer used in Erkin Vahidov’s poems, the poet’s skill in using words are analyzed on the basis of examples. The use of lexemes acquired through Arabic, Persian, and Russian languages ​​in the poem and their effectiveness has been scientifically researched based on examples